Cellulose Acetate Membranes characters Due To Additions Additive Monosodium Glutamate (MSG) - Dwi Indarti; I Nyoman Adi Winata; Heny Yunita Novianti (Jurnal ILMU DASAR, 2013)
This study purposed to determine the effect of MSG on the character of cellulose acetate membranes. This membrane preparation using phase inversion technique. The results showed that the higher the concentration of MSG, which is the character of membrane permeability coefficients and higher water flux, whereas for the character of the membrane density test and 100-200 kDa dextran rejection further down. To test the FTIR proved that there are no additives or solvents are trapped in a membrane. Keywords : Cellulose Acetate, phase inversion, MSG, FTIR